Nicolau syndrome following Intramuscular Diclofenac Injection: a case report and review of the literature - Yaser M Ata (17945264) (2023)
Nicolau syndrome (NS), also referred as embolia cutis medicamentosa and livedo-like dermatitis, is an uncommon complication followed by drugs administered intramuscularly, intraarticularly or subcutaneously. In this case report we present a case of a 65-year-old lady who had a single dose of diclofenac sodium as an intramuscular injection in her left buttock due to back pain that led to developing what known as NS. She was treated with surgical debridement, drain insertion and skin approximation with antibiotics for 2 weeks with daily sterile dressing. The wound healed completely with scarring. NS is a preventable outcome, thus, proper procedures and precautions should be taken during intramuscular medication administration. Healthcare providers should avoid unnecessary injections, be familiar with the complication and consider it as a potential diagnosis for severe localized pain after any injection. Other Information Published in: Journal of Surgical Case Reports License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jscr/rjad224